Assessing Annual Actual Evapotranspiration Based on Climate, Topography and Soil in Natural and Agricultural Ecosystems (2022)
Demertzi, K.; Pisinaras, V.; Lekakis, E.; Tziritis, E.; Babakos, K.; Aschonitis, V. Assessing Annual Actual Evapotranspiration Based on Climate, Topography and Soil in Natural and Agricultural Ecosystems. Climate 2021, 9, 20. https://doi.org/10.3390/cli9020020